2022
DOI: 10.1002/aesr.202200146
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Freestanding Thin Polyethylene Oxide‐Based Film as Artificial Solid–Electrolyte Interface to Protect Lithium Metal in Lithium–Sulfur Batteries

Abstract: Lithium–sulfur batteries (LSBs) that utilize sulfur and lithium (Li) metal as electrode materials are highly attractive for transportation applications due to their high theoretical gravimetric energy density. However, two major challenges currently impede the commercialization of LSB, which are the formation of Li dendrites and polysulfide shuttling. To mitigate these two effects, a protective film or artificial solid–electrolyte interface (SEI) can be applied directly to the Li‐metal surface. Herein, the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 63 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…Research and development of organic-based artificial SEI layers are playing a crucial role in enhancing the performance and safety of LSBs [90,91,[97][98][99][100][101]. Various studies have demonstrated that organic-based SEI layers can enhance the stability of Li metal anodes, minimize side reactions, and prevent dendritic growth, thereby extending the battery's cycle life.…”
Section: Organic-based Artificial Sei Layermentioning
confidence: 99%
“…Research and development of organic-based artificial SEI layers are playing a crucial role in enhancing the performance and safety of LSBs [90,91,[97][98][99][100][101]. Various studies have demonstrated that organic-based SEI layers can enhance the stability of Li metal anodes, minimize side reactions, and prevent dendritic growth, thereby extending the battery's cycle life.…”
Section: Organic-based Artificial Sei Layermentioning
confidence: 99%
“…Transportation of the Li anode from the dry room atmosphere (average dew point = −40°C to −45°C) to the SEM was conducted using a self-made SEM holder that opens in high vacuum. 20 The S cathodes were prepared in the same dry room onto usual SEM holders and put into a box which was then sealed under argon in an aluminum bag. To maintain a low exposure to the surrounding atmosphere, the S cathode samples were opened and quickly put into the SEM directly after the chamber was opened.…”
Section: Materials Characterizationmentioning
confidence: 99%
“…As a representative strategy, a protective layer is formed on the surface of Li, which should exhibit the following characteristics: chemical/electrochemical stability to electrolytes, high Li-ion diffusion rate, stability to LPSs, and flexible mechanical properties [38,[40][41][42][43]. However, even if an ideal protective layer exists, the uniform coating on the surface of Li for constructing a stable interface between the protective layer and Li remains an issue to be addressed.…”
Section: Application In Anodementioning
confidence: 99%